Challenges and impact of patient obesity in radiation therapy practice. Issue 3 (August 2020) - Winters, E.; Poole, C.
Abstract: Introduction: The prevalence of obesity is rapidly increasing globally and has tripled between 1975 and 2016. Obesity is reported within the literature as having a significant impact on medical practice, professionals, imaging departments and healthcare systems. It is not known how this epidemic will impact radiation therapists' working environment and practice. The aim of this study is to explore the perceived challenges and impacts of patient obesity on radiation therapy practice from the perception of radiation therapists. Methods: All radiation therapists working in the Republic of Ireland were invited to participate. Two focus groups were conducted with 6 and 7 participants respectively. A seven staged method of analysis, using a computerised long table approach was developed and used to analyse the data and create themes related to radiation therapists' perception of managing obese patients. Results: Perceived challenges from the radiation therapists were difficulties; (1) Setting up the patient (2) Imaging (3) communication and emotional impact. Conclusion: An array of concerns were raised during this research about the increase and impact of obese patients on radiation therapists working environment. This study suggests that obese patients can present additional challenges to radiation therapists' current work practices. It is imperative that we recognise the additional challenges this patient cohort add to daily workflow. Further research is needed to identify the common key issues and how to manage this specific patient group. Implications for practice: At the moment there are no specific management strategies/policies in place for managing obese patients; this study suggests that it is something we need to consider implementing as standard in radiation therapy departments.